293 A Reflection of Experience Gained in Emergency General Surgery During The COVID-19 Pandemic at A London University Hospital. (12th October 2021) - Angamuthu, N; Gilliland, J; Chowdhury, S; D'Souza, R; Hart, C; Knowles, J
Abstract: Background: During COVID-19, acute surgical services witnessed an overhaul of practice due to constraints on staff and resource (beds, imaging, and theater) availability. Fear of COVID-19, among general population potentially added to delay in patients seeking medical assistance. This study describes experiences of acute general surgery at a COVID-19 designated tertiary institution wherein elective surgical work was put on hold and emergency on-call rota was modified during the pandemic. Method: A retrospective analysis (March-April 2019 vs 2020) of the surgical work from a prospectively maintained surgical database during COVID-19 was performed. Results: Emergency surgical admissions during March 2020 vs 2019 was 106 vs 207. Comparing the workload March-April 2020 vs 2019, emergency referrals were 266 vs 341, operations performed 71 vs 92. 31.5% (84/266) of patients were tested for COVID and 30% (25/84) were positive. Emergency surgery was performed in 71 patients (including appendectomies (28), hernia repair(3), laparotomy(3), Hartman's procedure(3), hemicolectomy(7) and anterior resection with covering ileostomy(2)). In this group, a male preponderance was noted (M:F 1.84:1), the average age was 43.2 years (6-91), length of stay 4.8 days (<23 hours-34 days). In the operative group, the 30-day mortality was 4.23% (3/71) and the morbidity was 31%. Conclusions: With local changes, stopping elective services, modifying on-call rota, a surgical department can continue to be functional and offer emergency surgical service for a sustained period during a pandemic. During the COVID pandemic, the average number of referrals, admissions and surgeries were lower when compared to the non-covid period.